ANTI-VIRAL ACTIVITY OF INDIAN MEDICINAL PLANT JUSTICIA ADHATODAAGAINST HERPES SIMPLEX VIRUS: AN IN-VITRO STUDY - RAHUL CHAVAN; DEVANSHI GOHIL; VIRAL SHAH; DR. SWETA KOTHARI; DR. ABHAY CHOWDHARY (International Journal of Pharma and Bio Sciences, 2013)
The Herpesviruses are important human pathogens that can cause mild to severe lifelong infections with high morbidity. Alternate drugs such as ayurvedic drugs are now a day’s used for management of HSV infections due to the emergence of resistant strains.The aqueous and methanol extract from leaves of Justicia adhatoda, were used to study the cytotoxicity effect on Vero cell line by using MTT assay. The methanolic extract at 10mg/ml significantly inhibited formation of plaques in Vero cells infected with 100 pfu of HSV1 and 2 by 100%. Similarly, the aqueous extract at 10mg/ml inhibited the plaque formation by 100% and 86% for HSV1 and 2.These results suggest that this herbal extract has potent anti-viral agents against herpes simplex viruses that can be exploited for development of an alternative remedy for HSV infections.